Celogentin mimetics as inhibitors of tubulin polymerization. (17th December 2019) - Thombare, Varsha J.; Holden, James A.; Reynolds, Eric C.; O'Brien‐Simpson, Neil M.; Hutton, Craig A.
Abstract : Bicyclic analogues of celogentin C have been synthesized in which the side chain–side chain cross‐links are replaced by thioether bonds. Several of the simplified bicyclic peptides displayed potent inhibition of tubulin polymerization. Abstract :